2010
DOI: 10.1089/neu.2010.1535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Combined Therapeutic Regimen of 8-OH-DPAT and Environmental Enrichment after Experimental Traumatic Brain Injury

Abstract: When provided individually, both the serotonin (5-HT 1A )-receptor agonist 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT) and environmental enrichment (EE) enhance behavioral outcome and reduce histopathology after experimental traumatic brain injury (TBI). The aim of this study was to determine whether combining these therapies would yield greater benefit than either used alone. Anesthetized adult male rats received a cortical impact or sham injury and then were randomly assigned to enriched or standard (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
126
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 71 publications
(136 citation statements)
references
References 93 publications
9
126
1
Order By: Relevance
“…The second therapy in this combined treatment approach is the systemic administration of the serotonin 1A (5-HT 1A )-receptor agonist buspirone. A recent dose-response study from our laboratory showed that buspirone facilitated spatial learning in a well-established water maze task and reduced the size of TBI-induced cortical lesions (Olsen et al, 2012), which replicates the results of studies evaluating other 5-HT 1A -receptor agonists, such as 8-OH-DPAT Kline et al, 2002cKline et al, ,2004Kline et al, ,2007Kline et al, ,2010, and repinotan HCl (Kline et al, 2001). The advantage of evaluating buspirone in an experimental model of TBI is that it is used clinically as a treatment for anxiety and depression, and therefore safety and tolerability issues are well known (Chew and Zafonte, 2009).…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…The second therapy in this combined treatment approach is the systemic administration of the serotonin 1A (5-HT 1A )-receptor agonist buspirone. A recent dose-response study from our laboratory showed that buspirone facilitated spatial learning in a well-established water maze task and reduced the size of TBI-induced cortical lesions (Olsen et al, 2012), which replicates the results of studies evaluating other 5-HT 1A -receptor agonists, such as 8-OH-DPAT Kline et al, 2002cKline et al, ,2004Kline et al, ,2007Kline et al, ,2010, and repinotan HCl (Kline et al, 2001). The advantage of evaluating buspirone in an experimental model of TBI is that it is used clinically as a treatment for anxiety and depression, and therefore safety and tolerability issues are well known (Chew and Zafonte, 2009).…”
Section: Introductionsupporting
confidence: 74%
“…To reduce counting errors associated with falsepositive identification of dying neurons, the total number of CA1 and CA3 morphologically-intact neurons (i.e., those with a clearly defined cell body and nucleus) were counted using a Nikon Eclipse E600 microscope with a 40 · objective. For consistency and replication, the data are presented as the percent of total neurons in the ipsilateral (injured) CA1 and CA3 regions relative to the contralateral (uninjured) hippocampus, as previously reported Dixon et al, 1999;Hoffman et al, 2008;Kline et al, 2004Kline et al, ,2010Sozda et al, 2010).…”
Section: Histology: Quantification Of Hippocampal Neuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17] Several studies have shown that systemic administration of early-and-single (i.e., acute) as well as delayed-and-multiple (i.e., chronic) treatments with the 5-HT 1A receptor agonists repinotan HCL and 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT) confer neurobehavioral benefits after TBI. [18][19][20][21][22][23][24] More recently, buspirone, also a 5-HT 1A receptor agonist, has been reported to enhance cognitive performance as well as significantly reduce cortical lesion volume after TBI. 25,26 This therapeutic paradigm, however, has not been evaluated as a treatment for experimental pediatric brain injury.…”
Section: Introductionmentioning
confidence: 99%